“Propuesta de un Sistema de Gestión de Inventarios en la Clínica Veterinaria SIRA PETS en la ciudad de Sangolquí”. - Anagumbla Monga, Lizbeth Alexandra (2024)
The purpose of this study is to propose an Inventory Management System in the SIRA PETS Veterinary Clinic in the town of Sangolquí in order to establish effective control of stock, purchases, sales, stock levels and expiration dates through an IT system. A visual analysis of the establishment was made to identify internal problems, and using an Ishikawa Diagram, key problems were identified so as to come up with a possible solution to allow improvement in operational activity and management of veterinary medical supplies. The proposed study is presented as a mixed investigation since it adopts qualitative and quantitative data, applying tools such as observation and documentary review to assess the internal control of the clinic focused on inventories.The results allowed us to identify a deficiency in operations, as well as the lack of demand monitoring, due to inadequate supervision, evidenced by the absence of registry of products sold or used. Next, an ABC classification analysis was carried out by data inversion compiled in 2023, in which 381 samples were taken. The results show 157 products leading with 80% higher level of importance in terms of inversion, while 118 products pertain to classification B of 15% having moderate turnover and 107 to classification C with a low level of 5%, both positioning themselves with 20% using the Pareto diagram.